Character Education-Based Learning Video Media on Science Content for Fifth Grade Elementary School - Murti, Komang Guntur Wisnu; I Gede Margunayasa (International Journal of Elementary Education, 2022)
The lack of learning media causes teachers to have difficulty in explaining the material. So that students are less enthusiastic and have difficulty understanding the material in following the online learning process. This study aims to develop learning video media based on character education on the content of science theme 1 sub theme 2 in class V. The development model in this study is a 4D model which includes the stages of define, design, develop and disseminate. The subjects used were two material and media expert lecturers, two learning expert teachers, and 10 class students. The methods in collecting data are using interviews and questionnaire. The data analysis technique used is descriptive qualitative analysis and descriptive quantitative analysis. The results of the analysis obtained by the expert test results obtained an average of 3.9 with very good qualifications. The design expert test got very good qualifications with an average of 4.2, the media expert test results obtained an average of 4.3 with very good qualifications, the response results from practitioners with very good qualifications obtained a percentage of 90.5% and the student response results received qualifications very good percentage obtained 84%. This shows that the media developed is suitable for use in learning.